MENINGKATKAN KETERAMPILAN MENULIS MELALUI LINGKARAN PADA ANAK TUNAGRAHITA RINGAN - Wirna Eryenti Aries; armaini -; Ardisal - (Universitas Negeri Padang, 2018)
Abstract: Background of the study was a problem between two mentally disabled students at D2/C in SLB YPPLB Padang. The students had problem in wrote the vowels, the wrote at two line bookmarks, wrote over the line that have providen, and wrote abnormal size of letter.The methode of this study was class action study. This study used two periods of cycle time whichis each cycle consists of planning, implementation, observastion and reflection. The subject of this study were mentally disabled students. The assessment of this study was calculated the percentage of students ability to wrote the vowels. Basede on the result of this study, it was known that ability of the student to wrote vowels can be increased by using the circle help. The result of first ability test from student with ZK initial were 0%, be able by using help 13,33%, The result of first period cycle that using time for three days are 13,33%, be able by using help 13,33%, the second period cycle result that using time for two days were 40%, and be able by using help 16,66%. The result of first ability test from student with FR initial were 0%, be able by using help 10%, The result of first period cycle that using time for three days are 6,66%, be able by using help 13,33%, the secont period cycle result that using time for two days were 33,33%, and be able by using help 16,66%. Based on the data analysis can be exsplained that students ability to wrote vowels can be increased by using the circle help.